2002
DOI: 10.22358/jafs/67915/2002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the secretion pattern of growth hormone and insulin-like growth factor - I in sheep of two crossbreeds after dietary protein restriction

Abstract: The presented study was designed to evaluate the relationships between cross types of lambs and the pattern of GH and IGF-I secretion under conditions of standard and restricted protein feeding. The experiment was performed on two different cross types of female lambs: [(Merino x Romanov) x Suffolk], n=10, (MxR) and [(Merino x Finn) x Suffolk], n=9, (MxF). Lambs of both cross types were divided into two groups and fed on two isoenergetic diets, but containing different protein levels, for 16 weeks, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Generally, the pulsatile measures of GH differ between the sexes, being higher in males than females (Gatford et al, 1997). These values also depend on the breed (Wójcik-Gładysz et al, 2002) and level of nutrition . It has been suggested that the gradual age-related fall in GH release could be related to prepubertal processes leading to attainment of fertility (Suttie et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pulsatile measures of GH differ between the sexes, being higher in males than females (Gatford et al, 1997). These values also depend on the breed (Wójcik-Gładysz et al, 2002) and level of nutrition . It has been suggested that the gradual age-related fall in GH release could be related to prepubertal processes leading to attainment of fertility (Suttie et al, 1991).…”
Section: Discussionmentioning
confidence: 99%